Prior Experience and Social Class as Moderators of the Planning‐Performance Relationship in China's Emerging Economy. (5th September 2013) - Zhang, Yuli; Yang, Jun; Tang, Jintong; Au, Kevin; Xue, Hongzhi
Abstract : This study advances research on business planning by integrating and reconciling the institutional and strategic planning perspectives to explore the performance implications of both formal and informal business planning. We also examine how an entrepreneur's prior experience and social class shape the planning‐performance relationship. Using a dataset of two waves of interviews with 313 founders in China, we found that both formal and informal business planning can benefit new ventures. Interestingly, as a unique contingency factor in the Chinese context, social class moderates only the link between formal planning and performance, whereas prior work experience moderates the effects of both formal and informal planning on performance. Copyright © 2013 Strategic Management Society.